Chiral Bifunctional NHC–Guanidine Ligands for Asymmetric Hydrogenation - Gorai, Mahadeb; Teichert, Johannes F. (Synlett, 2023)
We report the synthesis of chiral N-heterocyclic carbene/guanidine bifunctional ligands from readily available amino alcohols. The resulting chiral bifunctional copper(I) complexes are active catalysts in an asymmetric hydrogenation of ketones. We show that the chiral linker unit can be employed for the transfer of stereoinformation.
Keywords: N-heterocyclic carbenes; guanidines; bifunctional catalysts; hydrogenation; asymmetric catalysis; copper catalysis